PERAN CORPORATE GOVERNANCE DALAM PENCAPAIAN TARGET FINANSIAL UNTUK MENINGKATKAN NILAI PERUSAHAAN - Erika, Civi; Kurniawan, Heri; Ayu Savitri, Mai (Jurnal Manajemen Dayasaing, 2025)
Having an appropriate organizational structure is crucial to improving the overall process of monitoring and optimizing productive resources. One way to achieve this is by enhancing oversight through the establishment of good corporate governance. Corporate governance aims to maintain balance, strengthen control systems to protect shareholders’ interests, and meet the expectations of other stakeholders. In essence, corporate governance is intended to increase the company's value by achieving specific targets projected each year.The objective of this research is to determine the role of corporate governance in achieving financial targets to enhance company value. A quantitative method is employed to describe the relationships in the study, using EViews 10 software for analysis. The sample consists of companies in the food and beverage sector over a three-year period from 2021 to 2023.This model adopts the fraud triangle theory, focusing on the pressure of financial targets. The underlying reason is that financial targets exert pressure on management to achieve them. Failure to meet these targets can result in negative market sentiment towards the company, and vice versa. While most studies use profitability and financial performance as mediating models, this approach—focusing on financial target pressure—has been less explored. Therefore, the researcher is interested in using this approach, as no previous studies have applied this mediation model.